Superstition as ideology in Iranian politics : Majlesi to Ahmadinejad - Rahnema, Ali. (Cambridge : Cambridge University Press, 2011)
'A superstitious reading of the world based on religion may be harmless at a private level, yet employed as a political tool it can have more sinister implications. As this fascinating book by Ali Rahnema, a distinguished Iranian intellectual, relates, superstition and mystical beliefs have endured and influenced ideology and political strategy in Iran from the founding of the Safavid dynasty in the sixteenth century to the present day. The endurance of these beliefs has its roots in a particular brand of popular Shiism, which was compiled and systematized by the eminent cleric Mohammad Baqer Majlesi in the seventeenth century. Majlesi, who is considered by some to be the father of Iranian Shiism, encouraged believers to accept fantastical notions as part of their faith and to venerate their leaders as superhuman. As Rahnema demonstrates through a close reading of the Persian sources and with examples from contemporary Iranian politics, it is this supposed connectedness to the hidden world that has allowed leaders such as Muhammad Reza Shah Pahlavi and Mahmud Ahmadinejad to present themselves and their entourage as representatives of the divine, and their rivals as the embodiment of evil'--
Includes bibliographical references (p. 307-311) and index.
Keywords: Ideology -- Iran -- History; Islam and politics -- Iran -- History; z; Political psychology -- Case studies; Superstition -- Religious aspects -- Islam; Iran -- Politics and government -- Psychological aspects